Peran Pranata adat Dalam Pencegahan Konflik Antara Kelompok Masyarakat Adat - I Putu Agus Arya Dauh; I Ketut Sukadana; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2020)
Customary order becoming a sociological aspect of institutionalized procedures for handling conflicts is a reality that still exists in Indonesian society. Indonesian people in general still apply the traditional values ​​that have been applied for a long time as role models in social life. Law Number 7 of 2012, has encouraged customary arrangements in the management and solved problems in the community. The issue to be discussed in this paper were the regulation of handling social conflicts in Indonesia according to Law No. 7 of 2012? and the role of traditional institutions in handling social conflicts in Indonesia's heterogeneous society. In this study the authors used a normative legal research method. This study use the socio-legal approach. The results of this study showed that the regulation of handling social conflicts according to Law No. 7 of 2012 Customary Institutions have a role in conflict prevention, conflict management, post-conflict handling between communities. The role of the customary community order in handling a conflict for Indonesian community groups increases or fosters tolerance and mutual respect for freedom in carrying out community activities. With the growth of tolerance, conflict between communities can be avoided